Yesterday and today of reading interventions in the Argentine press (Intercom - Brazilian Journal of Communication Sciences, 2023)
Letters from readers have been par excellence with the direct intervention of the reading public in the press. It is a non-journalistic space that questions specific problems and represents popular concerns. Currently, online comments in periodical publications fulfill that function in some way, but the forms of access have changed substantially in relation to those of the past, just as the modes of circulation of the press have changed. The proposal is to carry out an analytical approach of those interventions in periodical publications of rural towns in Argentina during the first half of the 20th century in rural spaces, with the objective of comparing them with the current dynamics of the digital era. It is then an exploratory work, which aims - through case studies - to carry out a comparative analysis of present and past reading intervention practices.
Keywords: Press; Rural; Argentina